Customer agility, market orientation, and brand image in the context of Chinese market - Junfeng, Wang; Zesheng, Yang; RuQiang, Lai (Frontiers in Psychology, 2022)
Customer agility (CA) and market orientation have been widely discussed in prior research. Also, the role of brand image in business making-decision has been emphasized. However, the current analysis lacks integrating the relationship among the three concepts. Thus, this study creatively creates a causal relationship model of CA, market orientation, and brand image. Finally, 289 valid samples from the managers in Chinese market was collected for further analysis by partial least squares structural equation modeling (PLS-SEM). The results show that market orientation can positively affect CA (both customer-sensing capability and customer-responding capability), and CA will further have a positive influence on brand image. Also, market orientation has a direct impact on brand image. Additionally, CA (both customer-sensing capability and customer-responding capability) will mediate the impact of market orientation on brand image. The research has both theoretical and practical contributions. From the theoretical perspective, the results contribute to enriching the brand theory, strategy management, and marketing research. From the practical perspective, the investigation enlightens managers to pay attention to the roles of CA implementation and market orientation strategies in enhancing their brand image.